Metabolism of Fructose to Oxalate and Glycolate - Knight, J. (2010)
Much attention has been recently directed at fructose consumption because of its association with obesity and subsequent development of chronic diseases. It was recently reported that an increased fructose intake increases the risk of forming kidney stones. It was postulated that fructose consumption may increase urinary oxalate, a risk factor for calcium oxalate kidney stone disease. However, conflicting results have been obtained in human studies examining the relationship between fructose metabolism and oxalate synthesis. To test whether fructose intake influences urinary excretions impacting kidney stone risk, healthy subjects consumed diets controlled in their contents of fructose, oxalate, calcium, and other nutrients. Subjects consumed diets containing 4, 13, and 21% of calories as fructose in a randomized order. No changes in the excretions of oxalate, calcium, and uric acid were observed. In vitro investigations with cultured liver cells incubated with (13)C-labeled sugars indicated that neither fructose nor glucose was converted to oxalate by these cells. Fructose metabolism accounted for 12.4 ± 1.6% of the glycolate detected in the culture medium and glucose 6.4 ± 0.9%. Our results suggest that mechanisms for stone risk associated with fructose intake may lie in factors other than those affecting the major stone risk parameters in urine.